Synthesis and characterization of 3-[N,N `-bis-3-(salicylidenamino)ethyltriamine] Mo(VI)O-2@SBA-15: a highly stable and reusable catalyst for epoxidation and sulfoxidation reactions - Lazar, Anish; Thiel, Werner R.; Singh, A. P. (RSC Advances, 2014)
The efficient and reusable oxidation catalyst 3-[N,N'-bis-3-(salicylidenamino)ethyltriamine] Mo(VI)O-2@SBA-15 has been synthesized by the anchoring of the 3-[N,N-bis-3-(salicylidenamino)ethyltriamine] ligand (L or Salpr) on the inner surfaces of organofunctionalized SBA-15 and subsequent complexation with Mo(VI) O-2(acac)(2). The physico-chemical properties of the functionalized catalysts were analyzed by elemental analysis, ICP-OES, XRD, N-2-sorption measurements, TG & DTA, solid state C-13, Si-29 NMR spectroscopy, FT-IR, Raman spectroscopy, XPS, DRS UV-Vis spectroscopy, SEM and TEM. XRD and N-2 sorption analyses helped to find out the morphological and textural properties of the synthesized catalysts and confirm that an ordered mesoporous channel structure was retained even after the multistep synthetic procedures. The (100), (110) and (200) reflections in SBA-15 provide hints of a good structural stability, the existence of long range ordering and a high pore wall thickness. TG and DTA results reveal that the thermal stability of (L)Mo(VI)O-2@SBA-15 was maintained up to 300 degrees C. The organic moieties anchored over the surface of the SBA-15 support were determined by solid state C-13 NMR and FT-IR spectroscopy. Further, solid state Si-29 NMR spectroscopy provides the information about the degree of functionalization of the surface silanol groups with the organic moiety. The electronic environment and the oxidation state of the molybdenum site in (L)Mo(VI)O-2@SBA-15 were monitored by Raman spectroscopy, XPS and DRS UV-Vis techniques. Moreover, the morphology and topographic information of the synthesized catalysts were confirmed by SEM and TEM imaging. The synthesized catalysts were evaluated in epoxidation and sulfoxidation reactions, and the results show that (L)Mo(VI)O-2@SBA-15 exhibits high conversion and selectivity towards epoxidation and sulfoxidation reactions in combination with high stability. The anchored solid catalysts can be recycled effectively and reused several times without major loss in activity. In addition, Sheldon's hot filtration test was also carried out.